Design and Development of Physics Learning Media of Three Dimensional Animation Using Blender Applications on Atomic Core Material - Nasir, Muhammad; Prastowo, Rizo Budi; Riwayani, Riwayani (Journal of Educational Sciences, 2018)
The Aims of this study is to design and build a three dimensionalanimated physics learning media on the atomic core material using blenderapplication for High School Physics learning media for atomic core materialis already exist but still in the form of two dimensions, so it less of visualizeactual concept. This research used three-stage of development research. Thefirst stage is the design stage of the media by using instructional designmodel type ADDIE. The second stage is the stage of media developmentusing the blender application. The third stage is the stage of validation andreliability. Respondents amounted to 54 people consisting of 5 experts(Expert), 11 teachers (user experts), 20 teachers (users) and 18 students(users). Aspects assessed are pedagogic, content and technical. Datacollection technique is questionnaire. The results showed the validity scoreof experts 4.515 which means the learning media is valid with very highcategory. The Cronbach alpha value of the teacher as user is 0.950 and fromstudent as user is 0.889. it indicated that the media is reliable.